The case of the missing carrot cake - Newman, Robin; Zemke, Deborah ([Berkeley, California] : Creston Books, 2015)
When Miss Rabbit's carrot cake goes missing on Ed's farm, Detectives Wilcox and Griswold do what it takes to track down the thieves.
Includes a recipe for carrot cake.
Ages 4-8.
edited hb 2015-06-16
Keywords: Animals -- Juvenile fiction; Farm life -- Juvenile fiction; Food -- Juvenile fiction; Detective and mystery stories; Lost articles -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Fiction; Farm life -- Fiction; Food -- Fiction; Mystery and detective stories; Lost and found possessions -- Fiction; Mice -- Fiction; Humorous stories